Topaz synthesis using Al2O3, Al(OH)3 or Al2Si2O5(OH)4 and color centers promoting its radioluminescence response - Trujillo Vazquez, E. (2017)
A first study on the radioluminescence (RL) response of topaz synthesized is reported. Using three alternative and different compact reactants separately, i. e., aluminum oxide, aluminum hydroxide and kaolinite, synthesis tests by chemical vapor deposition (CVD) were conducted varying systematically processing temperature and time, incidence angle, and atmosphere. Results show the feasibility to form topaz using the three types of reactants, in varying amounts of 60%, 100% and 47%, respectively. Synthesized topaz exhibits a variety of morphologies: fibers and rectangular bars using Al2O3, cross needle shape compacts using Al(OH)3 and needle-shape phases using Al2Si2O5(OH)4. Irradiation with 90Sr beta-source revealed that only samples prepared using aluminum hydroxide exhibit RL response. The emission band centered at 390 nm of thermally untreated samples and the lack of RL emission of samples treated thermally at 500 °C confirm that the RL response is due to the (H3O4)0 color centers. The RL response showing the highest RL intensity at 390 nm is promoted by processing at 700 °C for 90 min, used for sample H3. A set of reaction pathways for topaz formation using the three alternative compact reactants is proposed.